2017
DOI: 10.13044/j.sdewes.d5.0132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Engine Cooling Water Temperature on Performance and Emission Characteristics of a Compression Ignition Engine Operated with Biofuel Blend

Abstract: The temperature of the coolant is known to have significant influence on engine performance and emissions. Whereas existing literature describes the effects of coolant temperature in engines using fossil derived fuels, very few studies have investigated these effects when biofuel is used. In this study, Jatropha oil was blended separately with ethanol and butanol. It was found that the 80% jatropha oil + 20% butanol blend was the most suitable alternative, as its properties were closest to that of fossil diese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In terms of technical performance, biodiesel has its limitation of low temperature flow characteristics which may lead to clogging of fuel filters and/or choking of the injectors (Dwivedi et al, 2013). Researchers have found that high viscosity biodiesel at low temperature condition affects the engine performance, fuel consumption, emissions, and the engine components' function (Hossain et al, 2017;Chen et al, 2016). Concerning low temperature condition at cold places with potential temperature dropping below 15°C, three Malaysian highlands namely Cameron Highlands and Genting Highlands, in Pahang, and Kundasang, in Sabah, Malaysia have been exempted from selling B10 and continued to supply B7.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…In terms of technical performance, biodiesel has its limitation of low temperature flow characteristics which may lead to clogging of fuel filters and/or choking of the injectors (Dwivedi et al, 2013). Researchers have found that high viscosity biodiesel at low temperature condition affects the engine performance, fuel consumption, emissions, and the engine components' function (Hossain et al, 2017;Chen et al, 2016). Concerning low temperature condition at cold places with potential temperature dropping below 15°C, three Malaysian highlands namely Cameron Highlands and Genting Highlands, in Pahang, and Kundasang, in Sabah, Malaysia have been exempted from selling B10 and continued to supply B7.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…Other papers were published in the previous SDEWES special issues in this area, investigating similar topics, namely: analysis of the fuel injection timing and ignition position in a direct-injection natural gas engine [96], effects of engine cooling water temperature on performance and emission biofuel engines [97], biofuel pellet torrefaction [98], bio-oil production [99] and thermal treatment [100], advanced fuels for gas turbines [101], coal and biomass cofiring [102], optimization of the furnaces of the aluminum industry [103].…”
Section: Advanced Combustion Techniques and Fuelsmentioning
confidence: 99%
“…Система охолодження прямо визначає температуру охолоджуючої рідини, оливи, наддувочного повітря та ін. В джерелах [1,2,3] показано, що зміна температури охолоджуючої рідини в бік зростання призводить до покращення перетікання робочого процесу дизеля, зменшення витрати палива та скорочення шкідливого впливу на екологію.…”
Section: аналіз публікаційunclassified